Soil microbial necromass carbon contributions to soil organic carbon after three decades of citrus cultivation - Mei, Tangyingze; Zeng, Quanchao; Chen, Ruifeng; Tan, Wenfeng (Frontiers in Microbiology, 2025)
IntroductionCitrus is one of the most economically significant fruits globally, and soil organic carbon (SOC) plays a central role in maintaining soil health and fertility. Consequently, enhancing SOC content directly influences both the yield and quality of citrus crops. However, the sources of SOC in citrus orchards and their mechanisms of contribution remains poorly understood.MethodsThis study investigated citrus soils from orchards of varying planting ages by collecting 0–20 cm soil samples. We analyzed amino sugars, glomalin, particulate organic carbon (POC), and mineral-bound organic carbon (MAOC) to examine the source of microbial residue carbon and its contribution to SOC.ResultsThe results revealed a significant decrease in microbial residue carbon (MNC), fungal residue carbon (FNC), and bacterial residue carbon (BNC) with increasing orchard age (p < 0.05). Specifically, the MNC in 30-year-old citrus soils was reduced by 46.27% compared to 10-year-old soils, FNC decreased by 45.61%, and BNC by 48.91%. The proportion of microbial residue carbon within SOC significantly decreased as planting years increased (p < 0.05), from 76.82 ± 2.84% in 10-year-old citrus soils to 20.54 ± 4.70% in 30-year-old soils. Furthermore, soil pH, NO₃−-N and MAOC were the main factors controlling MNC. MNC showed a significant negative correlation with SOC, indicating a weakened microbial carbon pump function in citrus soils and an increased reliance on other carbon sources, such as plant-derived carbon. Although citrus cultivation had led to a decline in microbial residue carbon over time, it remained a primary source of organic carbon, with its contribution depending on the age of the orchard.DiscussionThese findings offered novel insights into the mechanisms through which intensive citrus cultivation influences microbial necromass contributions to SOC. This study also highlighted the negative impacts of long-term citrus cultivation on soil microbial necromass and offered recommendations for the rehabilitation of aging orchards.